Effect of endotracheal tube lidocaine instillation in prevention of smokers emergence coughing: sample of Iraqi patients undergoing emergency appendectomy - Jawad, Mohammed; Alsaady, Malath Azeez (International Journal of Research in Medical Sciences, 2017)
Background:Cough reflex is normal protective reflex but cause various complication during emergence from general anesthesia especially to smokers Methods: 300 patients of both sex enrolled in this study to have open emergency appendectomy. Patients divided into 4 groups. 50 non-smoker patients as control group. 50 smokers patient received no per operative efforts to reduce the incidence of postoperative cough, 100 smokers patient received 20 ml of 0.5% lidocaine dropped slowly into the endotracheal tube throughout the procedure, and 100 smoker patient received 20 ml normal saline dropped slowly into the endotracheal tube throughout the procedure. At the end of surgery, after extubation, the patient was considered to have cough if develops irritating cough or have 3 or more bucking. Results: Incidence of cough significantly decreased (p≤0.05) among smoking patients treated with lidocaine in relation to patients treated with normal saline, smokers without intervention. Conclusions: Instillation of lidocaine to endotracheal tube is effective method in reduction of smokers cough during emergence from general anesthesia.